Doctor on board? What is the optimal skill-mix in military pre-hospital care?. Issue 10 (15th September 2010) - Calderbank, Philip; Woolley, Tom; Mercer, Stuart; Schrager, Jason; Kazel, Mike; Bree, Stephen; Bowley, Douglas M
Abstract : Background: In a military setting, pre-hospital times may be extended due to geographical or operational issues. Helicopter casevac enables patients to be transported expediently across all terrains. The skill-mix of the pre-hospital team can vary. Aim: To quantify the doctors' contribution to the Medical Emergency Response Team–Enhanced (MERT-E). Methods: A prospective log of missions recorded urgency category, patient nationality, mechanism of injury, medical interventions and whether, in the crew's opinion, the presence of the doctor made a positive contribution. Results: Between July and November 2008, MERT-E flew 324 missions for 429 patients. 56% of patients carried were local nationals, 35% were UK forces. 22% of patients were T1, 52% were T2, 21.5% were T3 and 4% were dead. 48% patients had blast injuries, 25% had gunshot wounds, 6 patients had been exposed to blast and gunshot wounds. Median time from take-off to ED arrival was 44 min. A doctor flew on 88% of missions. It was thought that a doctor's presence was not clinically beneficial in 77% of missions. There were 62 recorded physician's interventions: the most common intervention was rapid sequence induction (45%); other interventions included provision of analgesia, sedation or blood products (34%), chest drain or thoracostomy (5%), and pronouncing life extinct (6%). Conclusion: MERT-E is a high value asset which makes an important contribution to patient care. A relatively small proportion of missions require interventions beyond the capability of well-trained military paramedics; the indirect benefits of a physician are more difficult to quantify.